SISTEM INFORMASI ABSENSI PEGAWAI PUSKESMAS TANJUNG RAJA BERBASIS ANDROID - Adelya Agustina; Evi Yulianingsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Android-based Health Center workforce attendance information system is a solution designed to manage and monitor the presence of workers at the Health Center. As a health institution that provides health services to the community, the implementation of attendance for workers at the Health Center is an orderly and accurate system to support smooth operations and quality of service to patients. This system was developed using the Android platform, with the aim of making it easier for workers to run attendance through their respective mobile devices. The main features provided include: Monitoring worker attendance and tracking in real-time so that attendance data can be easily accessed through the system interface. In addition, this system also supports work schedule management, where administrators can compile and update worker schedules that can be accessed by all workers according to needs.